Assessment of Firms' Financial Resilience against Pandemic and Disaster Shocks in Albania - World Bank (Washington, DC, 2022)
Over the period 2019–21, Albania had to confront dual shocks: the 2019 earthquake and the COVID-19 pandemic. Both had sizable impacts on the country’s economy. The COVID-19 pandemic took a heavy toll on an economy already affected by the earthquake in 2019. Key sectors were put in lockdown in the second quarter of 2020, and the economy suffered a severe contraction of -10.6 percent in gross domestic product (GDP). The pandemic hit the travel, tourism, and other services sectors first; then mobility restrictions and post-COVID-19 behavior changes affected firms’ supply and demand. Given the structure of the economy, the associated loss in sales and profits had a disproportionate effect on small and medium enterprises